2000
DOI: 10.1148/radiology.217.3.r00nv33678
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Thrombectomy System versus Pulse-Spray Thrombolysis for Thrombosed Hemodialysis Grafts: A Multicenter Prospective Randomized Comparison

Abstract: The hydrodynamic thrombectomy system is at least as efficacious and safe as pulse-spray thrombolysis but shortens thrombus treatment time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…Subsequently, other publications demonstrated equivalent efficacy of other devices when compared to thrombolytic therapy [5][6][7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, other publications demonstrated equivalent efficacy of other devices when compared to thrombolytic therapy [5][6][7].…”
Section: Introductionmentioning
confidence: 97%
“…Accepted treatments for acutely occluded access grafts include surgery and thrombolytic therapy/angioplasty [3]. Several mechanical thrombectomy devices have been developed recently in efforts to lessen the invasiveness and cost of surgery and decrease complications related to thrombolytic therapy [4][5][6][7]. One of the first mechanical thrombectomy devices to be developed, and the first to be approved for the US market, was the Amplatz thrombectomy device (ATD); however, the final results in the trial comparing the ATD with surgical thromboembolectomy (ST) to declot occluded DAG had yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…XCOIL TM uses a series of loops that are placed around the thrombus to "cocoon" the clot, and the loops are then retracted to keep the thrombus from fragmenting during withdrawal (11 , 20). Studies of the XCOIL TM using a pulsatile flow model, similar to that described by Müller-Hülsbeck et al (14), have demonstrated no significant fragmentation or distal embolization (unpublished communication). Distal embolization into the adjacent artery occurred in one case (5.5%).…”
Section: Xcoilmentioning
confidence: 52%
“…The AngioJet device is reported to have a 6% to 10% rate of hemorrhagic complications, distal embolization, and vessel dissection during arterial interventions (13). An 11% occurrence of adverse events has been reported with use of hydrodynamic thrombectomy devices during dialysis graft declot procedures (14). Current arterial thrombectomy devices have a 2%-18% rate of distal embolization (13,(15)(16)(17)(18)(19), including an 11% incidence of distal embolization for the Trellis device (Bacchus Vascular) (17).…”
Section: Xcoilmentioning
confidence: 99%
“…These results were much better than those for surgical thrombectomy alone [10,11]. In addition, the results of the hybrid method were much better than thrombolytic therapy alone [12][13][14][15]. Lee et al studied the practice of mechanical thrombectomy, with or without thrombolytic agents, and reported an immediate success rate of 89.3%, but at 4 m follow-up, the vascular access patency declined to 25.6% [16].…”
Section: Discussionmentioning
confidence: 99%